The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-26507/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Malaria parasites in macaques in Thailand: stump-tailed macaques (Macaca arctoides) are new natural hosts for Plasmodium knowlesi, Plasmodium inui, Plasmodium coatneyi and Plasmodium fieldi

Abstract: Background: Certain species of macaques are natural hosts of Plasmodium knowlesi and Plasmodium cynomolgi, which can both cause malaria in humans, and Plasmodium inui, which can be experimentally transmitted to humans. A significant number of zoonotic malaria cases have been reported in humans throughout Southeast Asia, including Thailand. There have been only two studies undertaken in Thailand to identify malaria parasites in non-human primates in 6 provinces. The objective of this study was to determine the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Plasmodium coatneyi is commonly found in long-tailed macaques (M. fascicularis), and unlike other simian parasites, P. coatneyi shares morphological features to P. falciparum (Fig. 1) (Eyles, 1963;Fungfuang et al, 2020). A detailed study conducted between 2011 and 2014 in 7 states of Malaysia showed 3 mono-infections (2.17%) of P. coatneyi among 645 samples that tested positive for malaria (Table 2) (Yap et al, 2021).…”
Section: Plasmodium Coatneyi Zoonosismentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmodium coatneyi is commonly found in long-tailed macaques (M. fascicularis), and unlike other simian parasites, P. coatneyi shares morphological features to P. falciparum (Fig. 1) (Eyles, 1963;Fungfuang et al, 2020). A detailed study conducted between 2011 and 2014 in 7 states of Malaysia showed 3 mono-infections (2.17%) of P. coatneyi among 645 samples that tested positive for malaria (Table 2) (Yap et al, 2021).…”
Section: Plasmodium Coatneyi Zoonosismentioning
confidence: 99%
“…All P. fieldi-infected patients had concurrent infections with other Plasmodium species and responded well to chloroquine or artemisinin-mefloquine combination therapy (Table 2) (Putaporntip et al, 2022). A study conducted in Thailand determining the prevalence of different Plasmodium species in NHPs reported that of 93 macaque blood samples examined, P. inui (35%) and P. fieldi (30%) were the most prevalent species in malaria-positive macaques, presenting them as the natural reservoir and a potential public health concern to the local population (Fungfuang et al, 2020). The geographical distribution of reported P. fieldi infections in humans is depicted in Fig.…”
Section: Plasmodium Fieldi Zoonosismentioning
confidence: 99%
“…Plasmodium knowlesi is considered a zoonotic malaria species as the parasite originally resides in a macaque host. The currently known hosts of P. knowlesi are the long-tailed macaque (Macaca fasicicularis), pig-tailed macaque (Macaca nemestrina), banded-leaf monkey (Presbytis melolophus) [2] and stumped-tailed macaque (Macaca arctoides) [3]. Thus, the transmission of P. knowlesi is a complex interaction between the macaque hosts, the Anopheline vectors and humans.…”
Section: Introductionmentioning
confidence: 99%